Nonlinear dynamics of the development-inequality nexus in emerging countries: The case of a prudential policy regime - Lindokuhle Talent Zungu; Lorraine Greyling; Nkanyiso Mbatha (Economies, 2022)
This study analyses the nonlinear dynamic impact of economic development on income inequality in a prudential policy regime in a panel of 15 emerging markets from 1985-2019. More importantly, we seek to extend the existing debate on this subject, with roots back to the seminal work by Kuznets and many others, and add a twist by introducing a distinction between a prudential regime (1985-1999) and a non-prudential regime (2000-2019), as well as the threshold level at which economic development reduces inequality, using Panel Smooth Transition Regression (PSTR). The Generalized Method of Moments and fixed-effect models will be used to support our baseline results. The PSTR model was adopted due to its ability to deal with features that cannot be accounted for in dynamic panel techniques, such as endogeneity, homogeneity, cross-country variability, and time instability within the model. We found evidence of a non-linear effect between the two variables, where the threshold was found to be US13,800, above which economic development reduces inequality in selected countries, and this further confirms the Kuznets inverted U-shape in both regimes. Macroprudential policies were found to trigger development-inequality relationships. Our evidence largely suggests that policymakers ought to formulate policies that aim to attract investment, which will then create job opportunities and foster an improvement in the stan-dard of living, and also should be abreast of the level of economic development before implementing macroprudential policies.
Keywords: 330; economic development; emerging markets; income inequality; prudential policies; PSTR model